Kemajuan Pendidikan dan Intelektual di Era Dinasti Abbasiyah: Masa Keemasan dan Pengaruhnya pada Peradaban Modern - Maslahah, Hanum Mir’atul (Maliki Interdisciplinary Journal, 2024)
The development of education during the Abbasid dynasty was rapid, marked by the emergence of many Islamic scholars, intellectuals and thinkers. The education system in this era reached its golden age thanks to great support from leaders who paid great attention to science and technology. Policies that supported education, massive movements in the pursuit of knowledge, and the existence of structured educational institutions attracted many people to study and conduct research, making a major contribution to the progress of civilization at that time. Islamic education, although it existed before the Abbasid dynasty, experienced significant development in this era with advances in various fields. An advanced system of educational institutions and a research culture that was encouraged, as well as the translation of foreign books, were the main factors in this progress. Islamic education during the Abbasid Dynasty changed the socio-cultural culture of society with a high spirit of seeking knowledge. This article discusses advances in science and technology during the Abbasid dynasty era, patterns of community life, the existence of Islamic educational institutions, as well as government policies that supported the peak glory of this dynasty in various fields. This research uses the Library Research method with a qualitative approach. Research is carried out by collecting various sources of relevant data, reducing data, and highlighting important points from various sources